Perceived Scarcity, Anxiety, And Government Interventions: Unraveling Panic Buying Behavior Among Consumers In The UAE - Walid Nimer Atwah, Mohammed; Azila Mohd Noor, Nor (Journal of Neonatal Surgery, 2025)
Although panic buying is rarely and inconsistently reported, it is recognized as an unpredictable human behavior that has persisted throughout history, frequently manifesting in response to significant emergency situations. The objective of this study is to investigate the factors that influence panic purchasing behavior among consumers in the United Arab Emirates. The objective of this study is to examine the influence of anxiety and perceived scarcity on panic buying behavior, the mediating effect of anxiety on the relationship between perceived scarcity and panic buying behavior, and the moderating effect of government interventions on the relationship between anxiety and panic buying behavior. The online survey-based data from 157 respondents was collected using a convenient sampling method in this quantitative investigation. Partial Least Square Structural Equation Modelling (PLS-SEM) was implemented to analyze the data. The results of the data analysis showed that panic buying behavior was significantly influenced by perceived scarcity and anxiety, while anxiety was also significantly influenced by perceived scarcity. Conversely, anxiety serves as a mediator between panic purchasing behavior and perceived scarcity. The moderating function of government interventions in the relationship between anxiety and panic buying behavior was not identified in this study. The findings underscore the significance of anxiety and perceived scarcity in the development of panic buying behavior, thereby presenting policymakers with implications for the regulation of panic purchasing among consumers.